Potensi Cash Waqf Linked Sukuk sebagai Instrumen Pemulihan Ekonomi Nasional Pasca Pandemi - Faiza, Nurlaili Adkhi Rizfa (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2023)
The need for large funds for National Economic Recovery after the Covid-19 pandemic requires various low-cost, high-efficiency, and sustainable instruments. This study aims to analyze the potential of Cash Waqf Linked Sukuk (CWLS) as an instrument for National Economic Recovery in Indonesia. Collaborating on Sukuk as an instrument that can mobilize funds and waqf with its unique nature can generate income and finance productive activities where returns or profits will be stored for future funding. This study uses an exploratory qualitative approach by reviewing and analyzing facts, expert opinions, theories, and previous research on CWLS and its development potential. This study found that the CWLS collaboration model can be an alternative to sustainable Islamic financial instruments in Indonesia and has the potential as an instrument to obtain cheap and easy funds to accelerate post-pandemic national economic recovery. This instrument is very suitable because it has high flexibility, appeals to the Muslim philanthropic middle class, and is sustainable alms from waqf to be distributed to beneficiaries.